Bottled banana puree from lacatan bananas (Musa saplentum Var. Lacatan) - Castro, Florinda A
ABSTRACT The study was undertaken to develop a bottled banana puree using fully ripe lacatan bananas. Developmental studies were done to establish standardized formulation and procedure for the banana puree. Product test performance of the banana puree versus fresh finely mashed lacatan bananas was conducted to determine the suitability of the product in chosen recipes requiring the use of bananas. The bottled banana puree was evaluated objectively by means of physico-chemical and microbiological tests. Results of these tests showed that a microbiologically safe and acceptable product could be made by lowering the pH of the puree to 4.1 and heating it at 180-200F. The results of the sensory evaluation using Descriptive Scoring and the 9-point Hedonic Rating Scale showed that the bottled banana puree had the characteristic banana color and flavor. Results of the product test performance in chosen recipes indicated that banana puree gave a more acceptable test products than thos utilizing the finely mashed lacatan bananas.